1998
DOI: 10.1038/sj.onc.1201760
|View full text |Cite
|
Sign up to set email alerts
|

The human hepatitis B virus transactivator X gene product regulates Sp1 mediated transcription of an insulin-like growth factor II promoter 4

Abstract: Human hepatitis B virus (HBV) is one of the causative agents of hepatocellular carcinoma (HCC). The virus encodes a 17 kDa protein, X, which is known to be a causative agent in the formation of HCC. An insulin-like growth factor-II (IGF-II) is expressed during the formation of HCC. Among the four promoters of the IGF-II gene, promoters 2, 3 and 4 become activated during the formation of HCC. The high frequency of detection of hepatitis B virus X (HBV-X) antigen in liver cells from patients with chronic hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 37 publications
5
53
2
2
Order By: Relevance
“…9A). HBx has been shown to interact with Sp1 and to affect its DNA binding activity (9). Studies with Sp1 mutated promoter sequences in human liver cells were not possible as we observed that these sites were indispensable for XPB basal expression; this is in agreement with an earlier study (42).…”
Section: Expression Of Tfiih In Hbx Transgenicsupporting
confidence: 82%
See 1 more Smart Citation
“…9A). HBx has been shown to interact with Sp1 and to affect its DNA binding activity (9). Studies with Sp1 mutated promoter sequences in human liver cells were not possible as we observed that these sites were indispensable for XPB basal expression; this is in agreement with an earlier study (42).…”
Section: Expression Of Tfiih In Hbx Transgenicsupporting
confidence: 82%
“…Several transcription factor responsive elements are present in both XPB and XPD promoters including Sp1, Oct, TATA box-binding protein, and ETS-1. The Sp1 transcription factor has been shown to be a specific target for HBx resulting in impairment of its DNA binding properties (9). To address a possible role for Sp1, we used the Drosophila cell line SL2 which has an Sp1-deficient background.…”
Section: Fig 9 Sp1 and Hbx Expression In Drosophila Sl2 Cellsmentioning
confidence: 99%
“…One possibility is the direct interactions of ets transcription factor with HBV-X resulting in the activation of p21 as in the case of Maguire et al (1991). Another possibility is the activations of ets binding to its binding site through the post-transcriptional protein modi®cations through signal transduction pathways (Lee et al, 1998b). It has been known that Ets1 and Ets2 are speci®c nuclear targets of Ras signaling events and that phosphorylation of a conserved threonine residue is a necessary molecular component of Ras-mediated activations of these transcription factors (Yang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The arrows indicate the DNase I cleavage products of the 7.2 Kb HindIII and 11.4 BamHI full-length fragments. A diagram showing the relative positions of the H19 gene (box), the two H19 endodermal enhancer elements described by Yoo-Warren et al (1988) (circles), relevant restriction sites, probes, and identi®ed hypersensitive sites (HS1 ± 4, indicated by vertical arrows) is reported in (a) cell proliferation (Zhang et al, 1996(Zhang et al, , 1998Lee et al, 1998;Caricasole and Ward, 1993;Drummond et al, 1992;Kim et al, 1992;Dugimont et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Di erential activation of these promoters has been observed in human and experimental cancers (Ueno et al, 1988;Zarrilli et al, 1994). Although several transcription factors involved in neoplastic transformation have been reported to bind and regulate in vitro-transfected IGF2 promoter fragments, no information has been obtained so far on the mechanisms responsible for the activation of this gene during in vivo carcinogenesis (Zhang et al, 1996(Zhang et al, , 1998Lee et al, 1998;Caricasole and Ward, 1993;Drummond et al, 1992;Kim et al, 1992).…”
Section: Introductionmentioning
confidence: 99%